Physico Chemical Factors Influencing Seaweed Colonization in Selected Coastal Areas Of Kerala, India - K. A. Hashim; M. Badusha (Journal of Stress Physiology & Biochemistry)
Seaweeds play extremely significant ecological roles in numerous marine communities. Seaweeds belonging to Chlorophyta, Rhodophyta and Ochrophyta were collected during course of the study period from the coastal areas of Kerala. The physico-chemical factors were also monitored. The present study indicated that the various environmental factors such as temperature, salinity, PH, oxygen and nutrients have influence on the diversity and distribution of sea weeds. In this study, the seaweed biomass was high when the seawater temperature ranged between 29°C to 30°C. The pH of the study area remained within the normal range. Several species of green algae cannot grow in high salinity. At the same time, some species of red algae and brown algae cannot grow in the low salinity. Most species of seaweeds require nutrients, Carbon, Nitrogen, and Phosphorous in specific ratios. Nitrogen is the element most frequently considered to limit growth of seaweeds. In general high diversity was observed during pre monsoon and post-monsoon at all stations. These seasons favoured the algal colonization.